"Provocation" as an Expert Term in Forensic Linguistics - V. O. Kuznetsov (Теория и практика судебной экспертизы)
The article addresses the category of “provocation” as a forensic term that is an interdisciplinary concept in between the legal legal and linguistic concepts of “provocation”. An expert term “speech provocation” has been developed through an expert analysis where the category of “provocation” has been considered from the legal, linguistic, and expert perspectives. As a part of the consideration of the concept in the expert aspect, the relationship between the legal and linguistic categories has been established. The author concluded that as an expert linguistic term in examinations in corruption cases, the term “speech provocation for an offer/payment of a bribe” is used. In this case, the speech provocation is interpreted as a verbal act which incites one of the communicators to commit an unlawful act – to bribe. That is the linguistic contents of the phenomenon legally called “crime provocation". The article also addresses the methodological aspect of the detection of speech provocation.